No country for young firms? Start-up dynamics and national policies - Calvino, Flavio; Criscuolo, Chiara; Menon, Carlo (Paris, 2016)
"This paper provides new cross-country evidence on the links between national policies and the growth patterns of start-ups. In particular, it compares for the first time the heterogeneous effects of national policies on entrants and incumbents, within the same country, industry, and time period. A number of key facts emerge. First, start-ups in volatile sectors and in sectors that exhibit higher growth dispersion are significantly more exposed to national policies than start-ups in other sectors. Second, start-ups are systematically more exposed than incumbents to the policy environment and national framework conditions. Third, the results suggest that timely bankruptcy procedures and strong contract enforcement are key to establishing a dynamic start-up environment."